A comparative and normative analysis of the remoteness test in the availability of significant remedies in international sales transactions - Beheshti, Reza (Sweet and Maxwell, 2016)
This article focuses on the remoteness of loss. It will be shown that the availability of damages under legal regimes created by the main international conventions, such as the United Nations Convention on Contracts for the International Sale of Goods, are essentially the same, although there are some wording dissimilarities in the rules dealing with the remoteness test. However, the implications of the absence of a remoteness test for the possibility of termination in the Sale of Goods Act 1979 will be explored. It will be argued that the Sale of Goods Act 1979 is more flexible and more effective in satisfying commercial buyers’ needs than might be assumed.